2018
DOI: 10.1155/2018/7290170
|View full text |Cite
|
Sign up to set email alerts
|

The Antiapoptosis Effect of Geum japonicum Thunb. var. chinense Extracts on Cerebral Ischemia Reperfusion Injury via PI3K/Akt Pathway

Abstract: Geum japonicum Thunb. var. chinense (GJ) is a type of wild vegetable found in China and other Asian countries; it has been reported that its extracts possess a neuroprotective effect against cerebral ischemia reperfusion (CIR) injury. The aim of this study is to explore the effect GJ extracts on transient focal CIR injury and neurons apoptosis and to clarify its possible underlying mechanisms in vivo. Our results indicated that pretreatment with GJ extracts significantly ameliorated the infarct volume, decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Our study results showed that EA activated the PI3K/ AKT pathway and increased the expression of GFAP (a characteristic marker of AS). The result was consistent with a published study using Geum Japonicum extracts to effectively treat CIRI through the PI3K/AKT pathway [38]. GFAP expression was not involved in the increase of infarct volume after an ischemic stroke [39].…”
Section: Discussionsupporting
confidence: 92%
“…Our study results showed that EA activated the PI3K/ AKT pathway and increased the expression of GFAP (a characteristic marker of AS). The result was consistent with a published study using Geum Japonicum extracts to effectively treat CIRI through the PI3K/AKT pathway [38]. GFAP expression was not involved in the increase of infarct volume after an ischemic stroke [39].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported that G. japonicum crude extract and its active compounds such as triterpenoids have anticoagulant [7], antioxidant [8], anti-HIV [9], angiogenic [10], and vasorelaxant [11] activities. Ou et al recently reported that G. japonicum extract has neuroprotective effects in the middle cerebral artery occlusion model via inhibition of inflammatory-mediated factors [12]. Nigaichigoside F1, isolated from G. japonicum, has been reported to alleviate hepatic steatosis in high-fat-diet-induced obese mice by regulating lipid metabolism genes [13].…”
Section: Introductionmentioning
confidence: 99%
“…A study found that activating PI3K / Akt signal pathway could inhibit the apoptosis of nerve and reduce the occurrence of blood-borne brain edema. A series of studies have shown that many Chinese herbal extracts play a protective role in IS through this pathway [62,63]. Another study found that Baicalein also decreased the LC3-II/LC3-I ratio and promoted phosphorylation of the PI3K/Akt/mTOR signaling pathway which implied inhibition of autophagy.…”
Section: Discussionmentioning
confidence: 98%